Wizard CD Plus and ProTaper Universal: analysis of apical transportation using new software - Giannastasio, Daiana; Rosa, Ricardo Abreu da; Peres, Bernardo Urbanetto; Barreto, Mirela Sangoi; Dotto, Gustavo Nogara; Kuga, Milton Carlos [UNESP]; Pereira, Jefferson Ricardo; Reis So, Marcus Vinicius (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2013)
Objective: This study has two aims: 1) to evaluate the apical transportation of the Wizard CD Plus and ProTaper Universal after preparation of simulated root canals; 2) to compare, with Adobe Photoshop, the ability of a new software (Regeemy) in superposing and subtracting images. Material and Methods: Twenty five simulated root canals in acrylic-resin blocks (with 20 degrees curvature) underwent cone beam computed tomography before and after preparation with the rotary systems (70 kVp, 4 mA, 10 s and with the 8x8 cm FoV selection). Canals were prepared up to F2 (ProTaper) and 24.04 (Wizard CD Plus) instruments and the working length was established to 15 mm. The tomographic images were imported into iCAT Vision software and CorelDraw for standardization. The superposition of pre- and post-instrumentation images from both systems was performed using Regeemy and Adobe Photoshop. The apical transportation was measured in millimetres using Image J. Five acrylic resin blocks were used to validate the superposition achieved by the software. Student's t-test for independent samples was used to evaluate the apical transportation achieved by the rotary systems using each software individually. Student's t-test for paired samples was used to compare the ability of each software in superposing and subtracting images from one rotary system per time. Results: The values obtained with Regeemy and Adobe Photoshop were similar to rotary systems (P>0.05). ProTaper Universal and Wizard CD Plus promoted similar apical transportation regardless of the software used for image's superposition and subtraction (P>0.05). Conclusion: Wizard CD Plus and ProTaper Universal promoted little apical transportation. Regeemy consists in a feasible software to superpose and subtract images and appears to be an alternative to Adobe Photoshop.
Keywords: Endodontics; Cone-beam computed tomography; Root canal preparation; Tooth apex